The influence of the medium composition on the biosurfactants produced by Lactobacillus paracasei - Vecino, Xanel (2016)
[Excerpt] Lactic acid bacteria is an interesting group of microorganisms for the production of biosurfactants. In addition, these bacteria are generally recognized as safe by the American Food and Drug Administration. An example is the Lactobacil/us paracasei that was isolated from a Portuguese dairy industry and has been previously reported by Gudina and collaborators [1] forthe production of biosurfactants.The biosurfactants produced by LAB are cell-bound biosurfactants contrarily to the most well-known extracellular biosurfactants produced by Pseudomonas or Bacillus species. The main bottleneck of their industrial production and application is related with the production and recovery costs. Therefore, many studies are focusing on the use of renewable agroindustrial wastes as carbon sources in the fermentative processes [2]. The aim of this work was the production and characterization of biosurfactants by L. paracasei using a lignocellulosic residue (vineyard pruning waste) as carbon source. The vineyard pruning waste was subjected to a fractionation process to obtain cellulose, which was next submitted to a saccharification step with enzymes in order to convert cellulose in a glucose-based fermentation media. Once this glucose solution was obtained, it was further supplemented with 1 O g/L of yeast extract and 1 O g/L of corn steep liquor. [...]